The Influence of Learning Environment and Reading Motivation on Public Reading Interest in TBM the Rimba Bulan Reading Room in Padang Panjang City - Sari, Nadilla Permata; Arini, Fitri Dwi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is motivated by the desire to analyze three main focuses, namely: (1) analyzing the combined influence of learning environment and reading motivation on reading interest, (2) analyzing the influence of each learning environment separately on reading interest, and (3) the influence of reading motivation on reading interest individually. This research was conducted at the Community Reading Park (TBM) Ruang Baca Rimba Bulan located in Padang Panjang City in the 2024/2025 academic year using an explanatory quantitative approach. The population in this study involved all TBM visitors, totaling 57 people. Through the use of the Slovin formula, a sample of 36 respondents was determined, taken randomly using the simple random sampling technique. The type of data used in this study is primary data, while data analysis was carried out using the multiple linear regression method using SPSS software version 25.0. This analysis includes classical assumption tests and hypothesis testing through F tests, t tests, and coefficient of determination tests. The regression equation obtained in this study is Y = 28.952 + 0.015X1 – 0.457X2 + e. The results of the F test produced a calculated F value of 2.052 with a significance level of 0.145 which is above the threshold of 0.05. This means that simultaneously, the variables of the learning environment and reading motivation do not have a significant effect on reading interest. Although theoretically both have a close influence on reading interest, statistical results show that the influence of both together is not strong enough to increase reading interest. Therefore, it is recommended that TBM visitors be more active in creating a learning environment that supports and strengthens internal reading motivation, in order to create a more optimal increase in reading interest.